Determinants and consequences of financial constraints facing firms in Argentina - Fanelli, José M. (2001)
Over the last ten years, profound structural changes have occurred in the Argentine economy, including the monetary and exchange rate regimes and the banking sector. In spite of structural reforms and the market friendly environment, evidence shows that financial constraints are still tight and that market segmentation is important. This research suggests that: (i) credit markets are markedly segmented, (ii) firms are dependent on owned funds; (iii) the volatility of the environment and external shocks affect the firms’ capital structure. We focus on micro data from Stock Exchange and Encuesta Nacional de Grandes Empresas to: (a) present the stylized facts characterizing the capital structure of Argentine firms based on the analysis of balance-sheet items; (b) assess the relevance of financial constraints on investment at the firm level; (c) obtain quantitative evidence of firm’s financial structure and choices; (d) investigate the effects of financial imperfections on different types of firms according to different sample splits; (e) evaluate the effects of macroeconomic volatility and shocks on firms’ financial structure.